Emergence of Emergency Logistics Centre (ELC): Humanitarian Logistics Operations at the Straits of Malacca - Jeevan, Jagan; Mohd Salleh, Nurul Haqimin; Md Hanafiah, Rudiah; Ngah, Abdul Hafaz (Transactions on Maritime Science, 2020)
Despite the apprehension of certain parties, the demand for maritime emergency logistics has emerged following the occurrence of maritime accidents around the world while trading activities are performed. The requirement of Emergency Logistics Centre (ELC) is crucial as part of the maritime disaster preparedness at the Straits of Malacca (SOM). The ELC prevents massive losses, should any disaster occur in the rough ocean. Based on unforeseen situations at sea, this paper explores the contributing factors of the ELC in proposing and improving strategies for Kuala Linggi seaport as an ELC. The Exploratory Factor Analysis (EFA) has been employed to achieve the objectives of this paper. The outcome of this paper indicates that resource availability, risk management, and geographical factors are the three key attributes that are substantially required to transform Kuala Linggi seaport into an ELC. Furthermore, disaster preparedness, ELC supply-chain management system, and safety procedures are the crucial components to enhance the operational efficacy at this seaport as an ELC. The findings of this research may contribute to the safety of the maritime route and disaster preparedness at the SOM.